2006
DOI: 10.1103/physrevb.74.132408
|View full text |Cite
|
Sign up to set email alerts
|

Optical observation of non-Fermi-liquid behavior in the heavy fermion state ofYbRh2Si2

Abstract: We report far-infrared optical properties of YbRh2Si2 for photon energies down to 2 meV and temperatures 0.4 -300 K. In the coherent heavy quasiparticle state, a linear dependence of the lowenergy scattering rate on both temperature and photon energy was found. We relate this distinct dynamical behavior different from that of Fermi liquid materials to the non-Fermi liquid nature of YbRh2Si2 which is due to its close vicinity to an antiferromagnetic quantum critical point.PACS numbers: 71.10. Hf, 71.27.+a, The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
(62 reference statements)
3
33
1
Order By: Relevance
“…This result is consistent with our previous optical studies of heavy fermion compounds. [25][26][27] Therefore, the anisotropic T opt implies that T K is also anisotropic. The similar anisotropic T K has been discussed in orthorhombic CeNiSn and CeRhAs, in which no magnetic phase transition takes place.…”
Section: 17)mentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with our previous optical studies of heavy fermion compounds. [25][26][27] Therefore, the anisotropic T opt implies that T K is also anisotropic. The similar anisotropic T K has been discussed in orthorhombic CeNiSn and CeRhAs, in which no magnetic phase transition takes place.…”
Section: 17)mentioning
confidence: 99%
“…The temperature dependence of the residual Drude weight is common to heavyquasiparticles, whose scattering rate declines with decreasing temperature. [25][26][27] Next, the anisotropic formation processes of the c-f hybridization gap and quasiparticle state are discussed. Figure 3(a) indicates the temperature dependence of the low-energy portion of the σ(ω) spectrum along all principal axes.…”
Section: 17)mentioning
confidence: 99%
“…A heavy fermion state arises upon the formation of coherence among heavy quasiparticles below a lattice coherence temperature. The latter has been shown to be characteristic for the temperature dependence of the far-infrared optical response in heavy fermion compounds like YbRh 2 Si 2 and YbIr 2 Si 2 [1,2,3]. The signature of the Kondo interaction itself was discussed in terms of a gap-like suppression in the far-infrared optical conductivity due to a conductionband (c)-f electron hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…3) In addition, a characteristic mid-IR peak is often observed in ð!Þ, which results from a c-f hybridized state far from E F . [103][104][105][106][107][108][109][110][111][112][113] So far, high pressure IR-SR studies of the f electron state have been reported for SmTe, 114) SmS, 115) YbS, 116) CeRu 4 Sb 12 , 117) and CeIn 3 . 118) Both SmS and YbS are divalent semiconductors at ambient pressure, but undergo pressure-induced transition to a metallic IV state.…”
Section: Rare-earth (''Heavy-fermion'') Compoundsmentioning
confidence: 99%